From the sea to the mountains - plant use in Adjara, Samegrelo and Kvemo Svaneti, Sakartvelo (Republic of Georgia), Caucasus - Bussmann, Rainer W; Paniagua Zambrana, Narel Y; Sikharulidze, Shalva; Kikvidze, Zaal; Darchidze, Maia; Manvelidze, Zurab; Ekhvaia, Jana; Kikodze, David; Khutsishvili, Manana; Batsatsashvili, Ketevan; Hart, Robbie E (Ethnobotany Research and Applications, 2020)
Background: Ajara, Samegrelo and Kvemo Svaneti are historical provinces of Georgia located on the south-facing macro-slope of the western part of the Greater Caucasus (Samegrelo and Kvemo Svaneti) and west of the Lesser Caucasus towards the Black Sea (Ajara). In this study we documented traditional plant use in Ajara, Samegrelo and Kvemo Svaneti. Methods: Fieldwork was conducted from July-August 2014 and June -November 2019. Interviews using semi-structured questionnaires were conducted with 84 participants (40 women and 44 men), with oral prior informed consent. Results: We encountered 276 plant species belonging to 181 genera of 88 vascular plant families, and 3 fungal species and 8x undetermined fungi of at least 9 genera, belonging to at least 7 fungal families, and 1 lichen being used in the research region. Of these 163 species were exclusively wild collected, 114 were grown in homegardens, and 18 were both grown in gardens and collected in the wild. Plants and their uses mostly overlapped among the areas within the region, with a slightly wider divergence in uses than in plants. Conclusions: The environmental fit analysis showed that a large degree of this variation was explained by differences among participant communities. The elevation of the participant community significantly fit the ordination in plant-space and explained a large degree of the variation in plant species reported but not in use-space. Gender was not significant in plant-space or use-space. Key words: Caucasus, ethnobotany, plant use, traditional knowledge, post-soviet development